Pharmacokinetic and metabolism study of ginsenoside Rb2 in rat by liquid chromatography combined with electrospray ionization tandem mass spectrometry. (23rd June 2021) - Wang, Wan; Ha, Li; Li, Xinyuan; Zheng, Weiwan; Yang, Encheng
Abstract: In this study, a simple and rapid ultra‐fast liquid chromatography tandem mass spectrometry method was established and validated to determine ginsenosides Rb2 in rat plasma. Acetonitrile‐mediated protein precipitant was applied to the sample preparation. Chromatographic separation was carried out on an Acquity UPLC HSS T3 column (100 × 2.1 mm, 1.8 μm). The analytes were monitored using multiple reactions monitoring mode with precursor‐to‐product ion transitions at m/z 1077.4–945.3 and m/z 799.8 → 637.8 for ginsenoside Rb2 and internal standard, respectively. The mobile phase was composed of 0.1% formic acid aqueous solution and acetonitrile. The assay showed excellent linearity over the concentration range of 2–1, 000 ng/ml, with correlation coefficient >0.995. The method was further validated for selectivity, precision, accuracy, recovery, and stability according to the US Food and Drug Administration guidelines. The validated method was successfully applied to pharmacokinetic and bioavailability studies of ginsenoside Rb2 in rat plasma. Based on the pharmacokinetic results, ginsenoside Rb2 showed slow clearance and low oral bioavailability (0.15%). In addition, the metabolites of ginsenoside Rb2 in rat urine and feces were characterized according to their accurate masses and fragment ions. The proposed metabolic pathway was deglycosylation.